Experimental research on design parameters of basin tuned and particle damper for wind turbine tower on shaker. Issue 11 (16th August 2019) - Chen, Junling; Wang, Yanchen; Zhao, Yong; Feng, Youquan
Summary: A basin tuned and particle damper is proposed to reduce the wind‐induced vibration for wind turbine tower. A shaker test platform was introduced to simulate the first‐order vibration of the wind turbine tower under the emergency shutdown case. The swing frequency of the shaker can be adjusted by changing its suspension length. The different vibration intensity of wind turbine system can be considered by setting the different initial displacement on the shaker test platform. A series of tests were carried out to study the influence of different parameters on the damping effect. The displacement response of the shaker test platform was measured by the laser displacement sensor. The whole test process was recorded by a camera installed aside the steel frame for watching the movement characteristics of steel balls in containers. The videos and test results show that the proposed damper can effectively increase the system damping ratio. The influence of different parameters, such as controlled frequency sensitivity, damper mass ratio, and the number of steel balls per container on the damping effect, was studied by single factor analysis. It is found that the proposed damper has the advantage of being insensitive to the controlled frequency and is available for wind turbine tower during its design reference period. The research can provide a reference for the optimal design and application of this type of damper.